Scratch as an Optimal Learning Media in Microlearning - Dewi, Evi Rosyani; Sari, Dewinta; Zulfikar, Nakeisha Diza (Journal of English Education and Teaching, 2025)
In the contemporary digital age, conventional pedagogical practices are transforming the microlearning approach, which disseminates content in discrete units to facilitate enhanced comprehension among learners. This article examines the potential of Scratch as an educational tool that can be employed to support the microlearning approach. Scratch is a block-based visual programming platform designed to facilitate beginners' learning of programming interactively. The utilization of Scratch across a range of educational levels has been demonstrated to enhance students' motivation, active engagement and learning outcomes. The findings of this literature review indicate that Scratch has the additional benefit of improving students' logical and creative thinking skills. Nevertheless, there are obstacles to the implementation of Scratch, including restricted access to technology and the necessity for teacher training to comprehend programming concepts. It is therefore evident that support from educational institutions and the government is crucial to realize Scratch's potential fully. By integrating Scratch into the microlearning framework, students can learn enjoyably and efficiently, thereby creating a more dynamic and relevant learning experience that is better suited to the needs of the digital age. This article aims to provide insight into the effectiveness of Scratch as a learning medium in the context of microlearning and to encourage further research on the application of technology in education.